CRISPR-Cas9: Tool for Qualitative and Quantitative Plant Genome Editing - Noman, Ali; Aqeel, Muhammad; He, Shuilin (Frontiers in Plant Science, 2016)
Genome editing advancements have made many unachievable ideas practical. Increased adoption of genome editing has been geared by swiftly developing CRISPR-Cas9 technology. This technique is appearing as driving force for innovative utilization in diverse branches of plant biology. CRISPR mediated genome editing is being used for rapid, easy and efficient alteration of indigenous genes among diverse plant species. With approximate completion of conceptual work about CRISPR/Cas9, plant scientists are applying this genome editing tool for crop attributes enhancement. The capability of CRISPR-Cas9 systems for performing targeted and efficient modifications in genome sequence as well as gene expression will certainly spur novel developments not only in model plants but also in crop plants. Additionally, due to non-involvement of foreign DNA, this technique may help alleviating regulatory issues associated with GM Plants. We expect that prevailing challenges in plant science like genomic region manipulation, crop specific vectors etc. will be addressed along with sustained growth of this genome editing tool. In this review, recent progress of CRISPR/Cas9 technology in plants has been summarized and discussed. We review potential of CRISPR/Cas9 for different aspects of plant life. It also covers strengths of this technique in comparison with other genome editing techniques e.g. ZFNs and TALENs and potential challenges in coming decades have been described.